A Reader In Animation Studies - Pilling, Jayne (Book collections on Project MUSE., 1997)
Cartoons-both from the classic Hollywood era and from more contemporary feature films and television series-offer a rich field for detailed investigation and analysis. Contributors draw on theories and methodology from film, television, and media studies, art history and criticism, and feminism and gender studies.